Global and regional evaluation of a global model simulated AODs with AERONET and MODIS observations. (11th December 2017) - Sheel, Varun; Guleria, Raj P.; Ramachandran, S.
ABSTRACT: Aerosol optical properties vary widely globally due to their short residence time and the large variability in their composition and size resulting from varying sources. In this study, we make use of the three‐dimensional global atmospheric chemistry transport model MOZART (Model for OZone And Related chemical Tracers), to simulate Aerosol Optical Depths (AODs) and compare with observations from MODIS (Moderate Resolution Imaging Spectroradiometer, level‐3) on board the Terra satellite and AERONET (AErosol RObotic NETwork level‐2), at regional and global scale for the period 2000–2007. The AOD values at a reference wavelength 550 nm are reported for all the data sets. Model and observations show intense aerosol burden over the parts of the world where developing countries are located. On a regional scale, varying features are noted for different regions depending upon topography, regional emissions and weather conditions. MOZART captures the general features observed in AERONET and MODIS fairly well; however, in biomass burning dominated regions (Central South America, South Africa, and North Australia) it underestimates the observed AOD. In industrial regions (North Europe and Mediterranean) MOZART overestimates the observations and over dust dominant regions (Saharan Africa, Middle East, and East Asia), the model AODs are comparable to AERONET and MODIS observations. In general, MOZART simulated AOD show similar seasonal and regional variability as observed in AERONET and MODIS. Our results are similar to the most commonly used models, i.e. GOCART (the GOddard Chemistry, Aerosol, Radiation, and Transport) and GEOS‐4 (Goddard Earth Observing System‐version 4). Abstract : Global distribution of seasonal mean aerosol optical depth at 550 nm. The data collected from MODIS (Moderate Resolution Imaging Spectroradiometer, level‐3) sensor on board of Terra satellite Collection 5.1 (product name 'MOD08_M3.051').